ANALISIS KEKUATAN LENTUR KAYU SENGON AKIBAT KONDISI TERENDAM AIR SUNGAI - Naeni, Heni Faidatul; Arnandha, Yudhi; Aswadi, Lalu Samsul (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2024)
Soaking wood is often done by traditional communities, including the people of Jogotamu Hamlet, Loano Village, Purworejo Regency, to preserve wood to be used as construction materials such as battens and formwork. Testing the flexural strength of sengon wood beams, which are low grade wood, were immersed in river water to see the effect of the bending strength of sengon wood due to being submerged in river water. The main objective of this research is to determine the physical properties (water content, density, and specific gravity), Modulus of Rupture (MoR), and Modulus of Elasticity (MoE). Flexural strength testing of sengon beams measuring 760 mm x 50 mm x 50 mm with guidelines based on SNI-03-3959-1995 with variations without soaking, 7 days soaking, 14 days soaking, 21 days soaking, 28 days soaking, and 35 days soaking Flexural strength testing was carried out at the Structure Laboratory of the Civil Engineering Department, Faculty of Engineering, Tidar University, Magelang. The test results produced an average value of water content without soaking, soaking for 7 days, 14 days, 21 days, 28 days and 35 days respectively, namely 14.65%, 31.85%, 36.21%, 31.85%, 33.37%, and 32.84%. The average density values are respectively 0.40 gr/cm3, 0.57 gr/cm3, 0.66 gr/cm3, 0.60 gr/cm3, 0.64 gr/cm3, and 0.61 gr/ cm3. The average values of specific gravity are 0.35, 0.43, 0.48, 0.46, 0.48, and 0.46, respectively. The average Modulus of Rupture (MoR) values were 24.77 MPa, 23.82 MPa, 22.75 MPa, 23.86 MPa, 23.73 MPa, and 25.47 MPa, respectively. Meanwhile, the average Modulus of Elasticity (MoE) values are 3,495.20 MPa, 3,382.14 MPa, 3,893.05 MPa, 4,316.36 MPa, 1,689.34 MPa, 2,899.42 MPa. Based on Anova analysis, soaking sengon wood during this period resulted in the conclusion that there was no significant difference or no effect.